The Construction of Religious Court Judges' Decisions in the Case of Joint Assets Based on Islamic Law and Legal Development - Isnawati Rais; Ya Rakha Muyassar (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2022)
In deciding joint property cases, religious court judges apply the provisions of Article 97 of the KHI with the division of 1/2–1/2 part of joint assets. However, in the decision No. 70/Pdt.G/2002/PA.Mrk, No. 330/Pdt.G/2004/PA.Tgrs, and No. 278/Pdt.G/2005/PA.Bkt, the judge of the religious court did not make a decision based on this provision. The Merauke PA decides the joint property case in a 4/10–6/10 division, the Tigaraksa PA 20%-80%, and the Bukittinggi PA 1/4–3/4. This study looks at the considerations and perceptions of the religious court judges in deciding joint property cases. The method used in this research is normative juridical which is qualitative in nature, using a comparative approach. As a result, the panel of judges in the 3 religious courts deviated from the applicable legal provisions, considering several factors. There are 5 factors that are considered by the panel of judges in deciding joint property cases, including: contribution factors, legal arguments, a sense of justice, legal arguments, origins of joint assets, and contextual understanding of a legal provision.